Optimizing pesticide spraying in high density apple orchards in South Africa, using Venturia inaequalis as model pathogen. - Rebel, Philip (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.